LEVELS OF FORMATION OF MOTIVATION TO STUDY - Makhmudjonov Asrorjon Bakhromovich (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, it is explained that it is appropriate to use situations of different forms and content to increase the strong motivation of students to learn, and for this, certain tasks should be set at each stage and methods of solving them should be defined.